Living with Tears - Adivasis in Kerala - Jiji Paul, S. (University of Jaffna, 2016)
The present study was conducted to evaluate the socio-economic and political background of the “Adivasi” communities in the state of Kerala. The term “Adivasi” refers to the indigenous people of India who possess distinct identities and cultures often linked to certain territories. The term is derived from the Hindi word “adi” which means “early times” or “original” and “vasi” means inhabitant or residents. More than one third of the Adivasis of Kerala State resides in Wayanad district and others are living Attappady area. Adivasi communities, numbering 136,062 (17.4% percent of the total population of the district) live in Wayanad district. They are made of Paniyan (44.8%t), Mullu Kuruman (17.5%), Kurichian (17.4%), Kattunaickan (9.9%), Adiyan (7.1%) and Urali Kuruman (2.7%). In Attappady more than 90 percent of the tribal population lives below poverty line. Kurumba a primitive tribal group in Kerala live under extreme poverty. Adiya, Paniya and Kattunaikan are the other tribal communities which are still seriously underdeveloped when compared with the other tribal groups. Adivasi communities are faced with high poverty, unemployment, internal displacement, lower levels of literacy and less access to health services. Most Adivasi live under poor hygienic condition. They faced with low life expectancy, low nutritional intake, high morbidity and high infant mortality rate. Human Right violations such as sex abuses are common in Adiviasi communities. In recent times, tribes in Attappady hills have received a high publicity due to the infant deaths in the tribal hamlets in Attappady district. Lifestyle and livelihood of most Adivasi are dependent on forest and agriculture. Adivasis have become landless due to the large scale migration of people from the other districts. As a result tribal people in Kerala have lost their cultural living style and freedom they were enjoying and are now living with tears. Climate changes impacts and environmental problems such as deforestation have worsened their case.
Keywords: Attappady; Living standards; Kerala; Poverty; Tribal communities